SUFFERING FROM ‘POLITICAL EXHAUSTION’: The Dynamics of Nahdlatul Ulama (NU) in Indonesia’s Political Arena (State Islamic University (UIN) of Sunan Ampel Surabaya, 2009)
Book Review:Book title:Nahdlatul Ulama and the Struggle for Power within Islam and Politics in IndonesiaAuthor:Robin BushNo. of Pages:xx + 236Year:2009Publisher:The Institute of Southeast Asian Studies, Singapore